The influence of learning style in introductory programming course of biology students - Mohamed, Noraini; Tarmuji, Nor Habibah; Mahiddin, Normadiah; Misman, Noraqilah (Journal of Islamic, Social, Economics and Development, 2025)
The critical role of learning styles in programming education is emphasizing the need for instructional approaches that accommodate the diverse ways students absorb, process, and retain information. Integrating learning styles such as visual, auditory, kinesthetic, and reading or writing into programming curricula can improve comprehension, retention, and engagement while fostering problem-solving skills and confidence. Despite the benefits, many programming education programs fail to address these varied learning preferences, leading to diminished understanding and preparedness for diverse work environments. This study aims to identify the relationship between learning styles and student performance, assessing the impact of tailored instructional methods on educational outcomes. Two out of four groups were randomly chosen using cluster sampling who enrolled in a C++ Basic Programming Course among B.Sc. (Hons) Biology students. VARK Questionnaires were distributed and the VARK score was determined for each participant. Meanwhile, the performance of students was determined by four assessments. The data were analyzed using Pearson’s correlation coefficient and the results indicate no relationship between learning styles and student performance. However, a significant moderate linear relationship was found between the different learning styles, suggesting the presence of collinearity between variables. This implies that a learner may favor more than two learning styles. This overlap can make it challenging to differentiate the impact of each learning style on educational outcomes, especially in research or when designing instructional methods tailored to specific learning preferences. Recommendations will be provided for effectively incorporating learning styles into programming courses, ultimately enhancing students' career readiness and establishing a stronger foundational programming knowledge.